Tanggung Jawab Digital Perusahaan di Indonesia: Sebuah Tinjauan Konseptual - Solihin (Jurnal Media dan Komunikasi, 2023)
The practice of Corporate Social Responsibility has been carried out massively since 2007. The existence of the Industrial Revolution 4.0 brought new challenges, namely digital transformation. This challenge become an evaluation for corporate social responsibility practices to change from traditional to digital one. This concept has known as Corporate Digital Responsibility. Unfortunately, the implementation of this concept must be adapted to each country. In Indonesia, implementing Corporate Digital Responsibility is a homework that must be completed by various stakeholders. By using a literature study, researchers want to describe the concept of Corporate Digital Responsibility from dimensions to conceptual frameworks. Researchers will also conduct case studies on the implementation of corporate digital responsibility by social media Twitter in Indonesia in the form of search prompts to help victims of gender based violence. The results show that the concept of corporate digital responsibility is present as a development of the concept of corporate social responsibility. Corporate digital responsibility includes four categories, namely social, economic, technological and environmental. Within the basic framework of corporate digital responsibility, there are four stakeholders who need to be involved to make corporate digital responsibility successful. In addition, the four main stages related to the technology life cycle also influence the success of corporate digital responsibility. The challenges of corporate digital responsibility practice in Indonesia are the absence of full authority for branch offices to adjust policies in force in the country, the low digital literacy of the Indonesian people, and the absence of a strong legal umbrella to serve as a guideline for implementing corporate digital responsibility.